Bioaccumulated Mercury by Several Types of Plants in Ex-Traditional Gold Processing Area, Gogorea Village, Buru Island - Mariwy, Abraham; Manuhutu, Julita B.; Frans, Defany (Indonesian Journal of Chemical Research, 2021)
This study examines the accumulation of metallic mercury by several types of plants in the traditional gold processing area in the village of Gogore, Buru district. The plants that were sampled in this study were guava, lempuyang gajah, and harendong bulu. These three plant species were chosen because they dominate the vegetation in the gold processing area. The analysis results showed that the lempuyang gajah was the plant that accumulated the highest mercury metal, namely in the roots of 16.79 ppm and the leaves of 15.03 ppm. Guava plants accumulated metal mercury in the roots and leaves of 11.73 ppm and 9.90 ppm, respectively. Meanwhile, harendong plants accumulated mercury in the roots and leaves of 2.59 ppm and 10.39 ppm, respectively. The BCF values ​​of guava, lempuyang gajah, and harendong bulu plants were 1.58, 0.41, and 0.39, respectively. Meanwhile, the TF values ​​of the three plants were 0.84, 0.89, and 4.01, respectively. From these results, it can be concluded that the three plants can accumulate mercury in high enough concentrations, so these three types of plants are categorized as hyper tolerant plants and accumulators.